Oxidative stress in major depressive and anxiety disorders, and the association with antidepressant use; results from a large adult cohort. Issue 5 (8th December 2016) - Black, C. N.; Bot, M.; Scheffer, P. G.; Penninx, B. W. J. H.
Abstract : Background: Oxidative stress has been implicated in the pathophysiology of major depressive disorder (MDD) and anxiety disorders and may be influenced by antidepressant use. This study investigated the association of oxidative stress, measured by plasma levels of F2-isoprostanes and 8-hydroxy-2′-deoxyguanosine (8-OHdG) reflecting oxidative lipid and DNA damage respectively, with MDD, anxiety disorders and antidepressant use in a large cohort. Method: Data was derived from the Netherlands Study of Depression and Anxiety including patients with current ( N = 1619) or remitted ( N = 610) MDD and/or anxiety disorder(s) (of which N = 704 antidepressant users) and 612 controls. Diagnoses were established with the Composite International Diagnostic Interview. Plasma 8-OHdG and F2-isoprostanes were measured using LC-MS/MS. ANCOVA was performed adjusted for sampling, sociodemographic, health and lifestyle variables. Results: F2-isoprostanes did not differ between controls and patients, or by antidepressant use. Patients with current disorders had lower 8-OHdG (mean 42.1 pmol/l, 95% CI 40.4–43.8) compared to controls (45.0 pmol/l, 95% CI 42.9–47.2; p < 0.001) after adjustment for sampling, sociodemographics and lifestyle, but these differences disappeared after further adjustment for antidepressant use ( p = 0.562). Antidepressant users had lower 8-OHdG levels (38.2 pmol/l, 95% CI 36.5–39.9) compared to controls (44.9 pmol/l, 95% CI 43.2–46.6; Cohen's d = 0.21, p < 0.001). Results for 8-OHdG were comparable across disorders (MDD and/or anxiety disorders), and all antidepressant types (SSRIs, TCAs, other antidepressants). Conclusion: Contrary to previous findings this large-scale study found no increased oxidative stress in MDD and anxiety disorders. Antidepressant use was associated with lower oxidative DNA damage, suggesting antidepressants may have antioxidant effects.